(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
For many nations, agricultural development not only meets the fundamental duty of the State to ensure the best possible in terms of access to food as one of the most important social rights in all societies. Beyond that, this essay seeks to demonstrate that this is an area that significantly impacts the behavior of subsequent secondary and tertiary sectors of the economy and may also be a mitigating factor in the consumer price index and unemployment, Which is the central subject of this article. However, the willingness of governments to invest substantial resources might not be enough when public policy in this regard, lacking a functional sense in the aggregation and articulation of these policies. The final reflection which arrives, suggests raising the measurement of impacts through the predictive modeling of public policies and interventions associated, which is essential to avoid wasting time, procrastination resources, lack of effectiveness in meeting the object of the respective policy and, perhaps can be more harmful to the political society, the alteration or loss of legal security and social peace.